Difference Between Watermelon Juice and Pure L-citrulline on Muscle Soreness After Eccentric Exercise: A Comparative Study - Nandyantami, Farah Fauziah; Ghozali, Dhoni Akbar; Munawaroh, Siti; Wiyono, Nanang; Muthmainah, Muthmainah (Faculty of Sport and Health Sciences, 2024)
Muscle overuse during exercise increases the risk of muscle injury. L-citrulline, one of the ergogenic substances highly found in watermelon, is frequently used to reduce muscle soreness. This study aimed to compare the effects of pure L-citrulline and watermelon juice in reducing delayed-onset muscle soreness (DOMS) and muscle damage using uric acid as a marker for inflammation. A single-blind controlled trial was employed among 33 participants selected with a purposive sampling method. The participants were given either a mineral water drink containing 1.2 g of L-citrulline supplementation, 750 ml of watermelon juice, or a bottle of mineral water as a placebo administered 2-h before exercise. A multiple-sprint with a deceleration phase was used to induce DOMS. There was a significant decrease of DOMS 12 h and 24 h post-exercise with watermelon juice and pure L-citrulline (p=0.001). However, there was no significant difference in effectiveness between both forms of supplementation (p = 0.748). There were no significant changes in uric acid levels post-exercise with both forms of supplementation. Both watermelon juice and pure L-citrulline show similar effectiveness in improving subjective feelings of DOMS but fail to provide evidence of their ability to reduce muscle inflammation significantly via the reduction of uric acid levels.